A Detailed Survey on Alarming growth of Obesity and Infertility - Kiran P, Rakshitha; Naveen, N C (International Journal of Computer Sciences and Engineering, 2025)
Obesity is a condition of being overweight. It’s a case where an individual weigh greater than healthy weight. Obesity and overweight have become a common problem of the entire population in the world. The effect of obesity in women’s health is eye-opening and undeniable which in turn is the main cause for women infertility. Obesity influences all the systems of our body including the reproductive system. The fact that obesity in infertile women is very high and there is a strong association between infertility and obesity. This paper shows increased rate of obesity and infertility over a decade. This paper also addresses the various cause for infertility in obese women.